Proses Pemecahan Sertifikat/Splitzing Tanah Pertanian Ditinjau Dari Risalah Pertimbangan Teknis Penatagunaan Tanah - Ihan Sri Wandari; Rizky Yuniansari; Arba Arba (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
This study aims to analyze the legal basis and function of the minutes of technical considerations in the transfer of rights to the process of splitting agricultural land certificates/splitzing and to find out the responsibility of the Mataram City Land Office for the issuance of the minutes of technical considerations. This research is a normative juridical research that examines the issue of the minutes of technical considerations of land use in the transfer of agricultural land rights below the minimum limit in accordance with the provisions of Article 9 paragraph (1) of Law Number 56 (Prp) 1960. The results of this study indicate that the basis for issuing the treatise of consideration technical documents in the form of an application for a permit to split agricultural land by the applicant, a statement of control/ownership of agricultural land, a statement from the seller and buyer that they will continue to use the agricultural land according to its function, a deed of sale and purchase (if any) or an underhand letter, a map of the suitability of land use with Mataram City spatial planning, field review by the land management division and original Ownership Certificate. The publication of the minutes is also based on the relevant laws and regulations. The function of the minutes of technical considerations in general can assist the community in completing land administration. While the responsibility of the Mataram City Land Office in the event of a dispute in the future against the land object, the responsibility is outside the realm of the Land Office because the responsibility is limited to the contents of the minutes regarding the analysis and conclusions of the land arrangement section and a statement letter by the seller-buyer/giver when the transfer of rights to land certificate/splitzing rights is transferred agriculture land